Traits of the resilient nurse. Issue 2 (March 2021) - Moore, Amy; Thal, Wendy
Abstract : The road to emotional resilience is often difficult, but it's through this process of overcoming or adapting that we grow. Abstract : The road to emotional resilience is often difficult, but it's through this process of overcoming or adapting that we grow.